Void swelling in ferritic-martensitic steels under high dose ion irradiation: Exploring possible contributions to swelling resistance. (February 2016) - Wang, Xu; Yan, Qingzhi; Was, Gary S.; Wang, Lumin
Graphical abstract: Swelling results of CNS preimplanted with 10 appm and 100 appm helium irradiated to 375 dpa and 450 dpa with 5 MeV Fe ++ at 460 °C. Abstract: Ion irradiations were performed on reduced-activation ferritic-martensitic steels CNS (China Nuclear Steel) I and CNS II up to 375 dpa and 450 dpa at 460 °C using 5 MeV Fe ++ ions with 10 appm and 100 appm pre-implanted helium. The swelling of 9Cr CNS I was 5.7–9%, while the 12Cr CNS II showed 20–300× less swelling than CNS I. Helium effects and possible contributions to swelling resistance in ferritic-martensitic steels were explored based on the results of transmission electron microscopy analysis. Radiation induced high density precipitates (Fe, Cr)2 C were found to account for the superior swelling resistance of CNS II.